Edukasi Dampak Penyakit Maag pada Remaja dan Cara Pengobatannya - ananda ramadani; Arief Azis; Agust Dwi Djajanti; Ainun Febrianti; Fitrah Ramadhani (JURNAL PENGABDIAN MASYARAKAT YAMASI, 2025)
This community service activity aims to provide education on the impact of gastric diseases in adolescents and their treatment methods. Gastric diseases, which include disorders of the digestive system such as gastric ulcers and gastritis, are often neglected by teenagers who are busy with daily activities and unhealthy eating habits. Through this program, we conducted socialization on the causes, symptoms, and long-term effects of untreated gastric diseases. In addition, participants were provided with information on effective treatment steps, including lifestyle changes, healthy eating habits, and the importance of medical consultation. The activities were carried out through interactive seminars, group discussions, and the distribution of easy-to-understand educational materials. It is hoped that this program will help adolescents better understand gastric diseases and raise awareness about the importance of maintaining digestive health from an early age to prevent more serious digestive disorders in the future.